Aplikasi Peminjaman dan Pengembalian Tools di Perusahaan PT. Esco Bintan Indonesia Berbasis Web - Liza Safitri (Jurnal Bangkit Indonesia, 2018)
In 1978, Esco was established in Singapore to provide clean air solutions for the high-tech and science industry website escoindonesia.com. From there, Esco is committed to providing the best solutions in technological capabilities to create a cleaner, healthier and safer world. In this study, which is used as an object of research that is in the system of borrowing and returning tools. In operational activities it still uses a manual and conventional system, unsupported by an integrated system. From the observations and research, the author finally built an Information System as solution. The information system is designed and built with a web-based platform using Notepad ++ as its programming editor, MYSQL front as a data base editor, XAMPP as a database server and PDF as a report viewer media. Apply the Squence Diagram method in software development. This new information system is expected to be able to assist in the company's activities, such as in making loan forms, return forms and loan and repayment reports, etc. The application of this Information System is expected to improve the efficiency, effectiveness and performance of the company PT Esco Bintan. After the existence of this Information System the company can operate this system more quickly and easily without requiring a very long time to operate the work. And the company is very easy to find the required documents and storage is very safe not easily lost